MoMoWo · 100 projects in 100 years European Women in Architecture and Design · 1918-2018 - Franchini, Caterina; Fernandez Garcia, Ana; Maria Garda, Emilia; Seražin, Helena (ZRC SAZU, Založba ZRC, 2016)
This publication is aimed to support two MoMoWo traveling exhibitions which will be presented in six European countries in two years (2016-2017): indoor exhibition catalogue "100 Works in 100 Years. European Women in Architecture and Design. 1918-2018", and outdoor exhibition "Women's Tale. A Reportage on Women Designers".Exhibition catalogue 100 Works in 100 Years. European Women in Architecture and Design. 1918-2018 brings together a selection of some of the most significant and representative examples of European architecture and design created by 100 women from the end of the First World War up until today. The number of works is symbolic, as 'one hundred' could also mean 'countless' as in the Latin word centium.